A Rapprochement between Feminist Ethics of Care and Contemporary Theology - Mannering, Helenka (Religions, 2020)
Ethics of care is a relatively new approach to morality, first developed as a feminist ethical theory in the 1980s by Carol Gilligan, Sara Ruddick, and Nel Noddings. It is based on the experience and responsibility of providing care and is distinct from other popular moral philosophies including Kantian moral theory, utilitarianism, or virtue ethics, although it has some similarities to virtue ethics. Founded on a relational ontology, it offers a deeply incisive critique of liberal individualism through ethical reflection. It is also committed to a particularism which recognises the importance of addressing moral problems in the context of lived experience. In this article, after an analysis of the foundational perspectives of care ethics, it will be contended that its central tenets tie in with contemporary approaches in theology, particularly those expressed in the writings of St John Paul II and Benedict XVI. Furthermore, it will be suggested that the anthropological and moral insights of these theologians can offer the ethics of care a deeper ontological and epistemological grounding, hence strengthening its viability and existential appeal.